Evaluation of the Proficiency of Distinguished Countries in Managing COVID-19 - Hamid Babaei-Meybodi; Hoda Moradi; Mehdi Abbaszadeh (مدیریت اطلاعات سلامت, 2021)
Introduction: The outbreak of coronavirus disease 2019 (COVID-19) has become one of the important global challenges. According to World Health Organization (WHO), a long-term challenge is ahead. This study endeavored to investigate the performance of distinguished countries in the management of Covid-19 in two areas of disease control and treatment.